Modern art - pedagogical technologies in a context of vocational training of the future teachers of music in higher educational institutions (Pedagogy of Higher and Secondary Education, 2009)
In article the contents of concepts Із systematized: "educational technologies", "pedagogical technology», "suggestive-pedagogical technology", their contents and structure is opened, application of receptions and methods which will promote efficiency to educational process, is offered to development of imagination, self-control and self-expression.
Keywords: technology educational technologies; pedagogical technology; art-pedagogical technology; vocational training; suggestive-pedagogical technology; future teacher of music